(untitled) (Research, Society and Development, 2020)
This article aims to present and describe the results of a case study developed from a clinical psychodiagnosis performed with a women of adult age, in the context of a school-clinic, located in a private university in the interior of Rio Grande do Sul – RS. In order to achieve the objectives, a total of eight psychological sessions were perfomed, where screening, anamnesis, testing and oral return happened. As a testing instrument, to point out the patient’s strengths and weaknesses, it was used the Personality Factorial Battery - BFP, clinical interviews and clinical observation. The methodology adopted was a unique and systematic exploratory case study. As a result, from the psychodiagnosis, it was possible to gather information about the patient’s life history, understand and evaluate her personality and the significant influence of the family on the decision-making processes of the examiner. This process allowed for therapeutic indication so that the patient’s needs were adequately met.